Contemporary Tourism and Temporal Models of the City: from the “Monument-logo” to the “Moment-logo” - Virgolin, Luigi (E|C, 2022)
The tourist discourse creates and stabilizes individual and collective identities, it suggests simulacra and forms of life, it makes translations between semiospheres. Travel communication models the physiognomy of places, local communities and tourists, continually redefining its language. This contribution formulates a theoretical proposal to put in evidence some trends of contemporary tourism discourse in relation to the cultural heritage of the urban space. The analysis of the semantic transformations of the monument underlines the change into the relationship between monumentality and the city in favor of a dynamic and contemporary urban identity. More generally, the tourist promotion of the urban space prefers the ordinary experience, a punctual temporal aspectuality and a form of life increasingly oriented to the practices of everyday life. The contribution is based on the recent tourist communication of Rome, whose Strategic Plan aims to build a different semiotic personality of the city.